Assessment of Radioactivity for Selected Regions in Wasit and Al-Anbar Governorates - Hayder Ahmed Hasaan; Zeki Abd-Jaber Algaisy; Omer Mhommod Marbit; Hadi Mohmmed Jaber; Takrid M. Nfae (Journal of Madenat Alelem University College, 2011)
The objective of this research was to assess the radioactivity for six selected areas in Wasit governorate and three selected areas in l Al-Fallujah district, Al-Anbar Governorate. The selected regions in Wasit governorate are (Center of Province Council, Al-khachea, Aastern, Center of Teaba Healthy, Al-Aseseey district, and Al-Aezezey district),and the selected areas areas in Al-Fallujah district are ( Al-Jawlan, Al- Sheheada, Al-Jeabeal). The dose and contamination rates in Al-Anbar governorate ranged between (0.02-0.04) µSv/h and (58-75) c/sec respectively. While the dose and contamination rates in Waist governorate ranged between (0.086-0.12) µSv/h, (0.66-0.78)c/sec respectively. The radiological analyses of the collected soil samples were measured by using gamma spectrometry (which consist of High- purity Germanium Detector) with a efficiency of 40% and resolution 2 keV for Energy, 1.33Mev,of 60Co. Collection, preparations and tests of soil samples were done according to IAEA procedures. The results indicated that the activity concentration of natural radionuclides in the series of U-238 and Th-232. In order to evaluate the radiological hazard of the natural radioactivity the software ReCLAIM version 3.0 was used ,the maximum annual effective dose was 0.31 mSv in Al-Fallujah district and 0.37mSv in Waist governorate these doses are lower than the annual dose limit for the member of the public recommended by the International Atomic Energy Commission (IAEA), thus there was no increase in radioactivity in selected areas.